Part-Time Work, Gender and Job Satisfaction: Evidence from a Developing Country - Lopez Boo, Florencia; Madrigal, Lucia; Pages, Carmen (2012)
This paper investigates the relationship between part-time work and job satisfaction in Honduras. In contrast to previous work for developed countries, this paper does not find higher job satisfaction among women working part-time. Instead, for both women and men, job satisfaction is higher when in full-time work, although this finding is stronger for men. Consistent with an interpretation of working part-time as luxury consumption, the paper finds that partnered women with children, poor women or women working in the informal sector are more likely to report higher job satisfaction when working full-time than single women, partnered women without children, non-poor women or women working in the formal sector.